Kinetics Study of Oxidative Desulfurization of Real Diesel Fuel Over Uncoated and Coated Nano-catalysts in an Oscillatory Helical Baffled Reactor - Amer Nawaf; Basma Abdul Majeed (Journal of Chemical and Petroleum Engineering)
The oxidative desulfurization (ODS) of real diesel fuel (RDF) was evaluated in a modified design oscillatory helical baffled reactor (OHBR). Peracetic acid was produced from hydrogen peroxide and acetic acid and used as an oxidant. Following that, a new design was made using nano-catalyst (uncoated and coated). The experimental work of the oxidative desulfurization process was utilized in an oscillatory helical baffled reactor under moderate conditions: residence times 3-9 min, oxidation temperatures 50-80 ℃, amplitude of oscillation 2-8 mm, and frequency of oscillation 0.5-2 min with 0.4 g of nano-catalyst with constant pressure. The optimal conversion of sulfur was 98.42% for the uncoated catalyst and 96.57% for the coated catalyst under 80 ℃, 8 mm, and 2.5 Hz. The purpose of this manuscript is to determine the ODS kinetic parameters and sulfur compound concentration profile in RDF. The model developed was according to the properties of the real diesel fuel, types of nano-catalysts, and operation conditions inside the OHBR based on the experimental observations. The optimal kinetic model and the half-life period of the nano-composites for the pertinent reactions have also been examined. This study also estimates the best kinetic model parameters of the oxidation reactions using the pseudo-first-order technique, which is based on the experimental data.